Models for the analysis of growth curves for rearing tinamous (Rhynchotus rufescens) in captivity - Tholon,P (2007)
Growth curves models provide a visual assessment of growth as a function of time, and prediction body weight at a specific age. This study aimed at estimating tinamous growth curve using different models, and at verifying their goodness of fit. A total number 11,639 weight records from 411 birds, being 6,671 from females and 3,095 from males, was analyzed. The highest estimates of a parameter were obtained using Brody (BD), von Bertalanffy (VB), Gompertz (GP,) and Logistic function (LG). Adult females were 5.7% heavier than males. The highest estimates of b parameter were obtained in the LG, GP, BD, and VB models. The estimated k parameter values in decreasing order were obtained in LG, GP, VB, and BD models. The correlation between the parameters a and k showed heavier birds are less precocious than the lighter. The estimates of intercept, linear regression coefficient, quadratic regression coefficient, and differences between quadratic coefficient of functions and estimated ties of quadratic-quadratic-quadratic segmented polynomials (QQQSP) were: 31.1732±2.41339; 3.07898± 0.13287; 0.02689±0.00152; -0.05566±0.00193; 0.02349±0.00107, and 57 and 145 days, respectively. The estimated predicted mean error values (PME) of VB, GP, BD, LG, and QQQSP models were, respectively, 0.8353; 0.01715; -0.6939; -2.2453; and -0.7544%. The coefficient of determination (R²) and least square error values (MS) showed similar results. In conclusion, the VB and the QQQSP models adequately described tinamous growth. The best model to describe tinamous growth was the Gompertz model, because it presented the highest R² values, easiness of convergence, lower PME, and the easiness of parameter biological interpretation.